DIABETES REMISSION RATE IN DIFFERENT BMI GRADES FOLLOWING ROUX-EN-Y GASTRIC BYPASS - COELHO,Daniel (2018)
ABSTRACT Background: Type 2 diabetes mellitus has a high long-term remission rate after laparoscopic Roux-en-Y gastric bypass (LRYGB), but few studies have analyzed patients with BMI<35 kg/m2. Aim: To compare glycemic control after LRYGB between BMI 30-35 kg/m2 (intervention group or IG) and >35 kg/m2 patients (control group or CG) and to evaluate weight loss, comorbidities and surgical morbidity. Methods: Sixty-six diabetic patients (30 in IG group and 36 in CG group) were submitted to LRYGB. Data collected annually after surgery were analyzed with generalized estimating equations. Results: Average follow-up was 4.3 years. There was no statistical difference between groups using complete remission American Diabetes Association criteria (OR 2.214, 95%CI 0.800-5.637, p=0.13). There was significant difference between groups using partial remission American Diabetes Association criteria (p=0.002), favouring the CG group (OR 6.392, 95%CI 1.922-21.260). The higher BMI group also had lower HbA1c levels (-0.77%, 95%CI -1.26 to -0.29, p=0.002). There were no significant differences in remission of hypertension, dyslipidemia and surgical morbidity, while weight was better controlled in the IG group. Conclusion: No differences were found in diabetes complete remission, although greater partial remission and the lower levels of glycated hemoglobin in the BMI >35 kg/m2 group suggest a better response among more obese diabetic patients with LRYGB. In addition, both groups had important metabolic modifications at the expense of low morbidity.